Submesoscale processes promote seasonal restratification in the Subantarctic Ocean. Issue 4 (8th April 2017) - du Plessis, M.; Swart, S.; Ansorge, I. J.; Mahadevan, A.
Abstract: Traditionally, the mechanism driving the seasonal restratification of the Southern Ocean mixed layer (ML) is thought to be the onset of springtime warming. Recent developments in numerical modeling and North Atlantic observations have shown that submesoscale ML eddies (MLE) can drive a restratifying flux to shoal the deep winter ML prior to solar heating at high latitudes. The impact of submesoscale processes on the intraseasonal variability of the Subantarctic ML is still relatively unknown. We compare 5 months of glider data in the Subantarctic Zone to simulations of a 1‐D mixing model to show that the magnitude of restratification of the ML cannot be explained by heat, freshwater, and momentum fluxes alone. During early spring, we estimate that periodic increases in the vertical buoyancy flux by MLEs caused small increases in stratification, despite predominantly down‐front winds that promote the destruction of stratification. The timing of seasonal restratification was consistent between 1‐D model estimates and the observations. However, during up‐front winds, the strength of springtime stratification increased over twofold compared to the 1‐D model, with a rapid shoaling of the MLD from >200 m to <100 m within a few days. The ML stratification is further modified under a negative Ekman buoyancy flux during down‐front winds, resulting in the destruction of ML stratification and deepening of the MLD. These results propose the importance of submesoscale buoyancy fluxes enhancing seasonal restratification and mixing of the Subantarctic ML. Key Points: Seasonal restratification defined using ocean glider observations cannot be explained by seasonal warming alone Up‐front winds and increased ML horizontal buoyancy gradients promote restratification by submesoscale ML eddies in spring Fluxes of wind‐driven Ekman buoyancy flux at horizontal buoyancy fronts compete with restratifying ML eddies to mix the upper ocean